Foreign cry1Ac gene integration and endogenous borer stress-related genes synergistically improve insect resistance in sugarcane - Zhou, Dinggang (BMC Plant Biol, 2018)
BACKGROUND: Sugarcane (Saccharum spp. hybrids) is considered the most globally important sugar-producing crop and raw material for biofuel. Insect attack is a major issue in sugarcane cultivation, resulting in yield losses and sucrose content reductions. Stem borer (Diatraea saccharalis F.) causes serious yield losses in sugarcane worldwide. However, insect-resistant germplasms for sugarcane are not available in any collections all over the world, and the molecular mechanism of insect resistance has not been elucidated. In this study, cry1Ac transgenic sugarcane lines were obtained and the biological characteristics and transgene dosage effect were investigated and a global exploration of gene expression by transcriptome analysis was performed. RESULTS: The transgene copies of foreign cry1Ac were variable and random. The correlation between the cry1Ac protein and cry1Ac gene copies differed between the transgenic lines from FN15 and ROC22. The medium copy lines from FN15 showed a significant linear relationship, while ROC22 showed no definite dosage effect. The transgenic lines with medium copies of cry1Ac showed an elite phenotype. Transcriptome analysis by RNA sequencing indicated that up/down regulated differentially expressed genes were abundant among the cry1Ac sugarcane lines and the receptor variety. Foreign cry1Ac gene and endogenous borer stress-related genes may have a synergistic effect. Three lines, namely, A1, A5, and A6, were selected for their excellent stem borer resistance and phenotypic traits and are expected to be used directly as cultivars or crossing parents for sugarcane borer resistance breeding. CONCLUSIONS: Cry1Ac gene integration dramatically improved sugarcane insect resistance. The elite transgenic offspring contained medium transgene copies. Foreign cry1Ac gene integration and endogenous borer stress-related genes may have a synergistic effect on sugarcane insect resistance improvement. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-018-1536-6) contains supplementary material, which is available to authorized users.